KEEFEKTIFAN METODE PERMAINAN MONOPOLI MATERI OPERASI HITUNG TERHADAP MINAT DAN HASIL BELAJAR SISWA KELAS I SD NEGERI 1 KEDUNGSUREN KENDAL - A.Y Soegeng; Sri Kartika Sinta Dewi (Universitas PGRI Semarang, 2013)
This research is motivated by a number of students that scored below the KKM is because teachers still use the lecture method. The problems revealed in this study is whether the methods of effective monopoly media-assisted game against the interest and learning outcomes of students in grade I arithmetic operations SD Negeri 1 Kedungsuren Kendal?. Statistical hypothesis in this study is whether there are differences in mathematics achievement using the lecture method using assisted game media monopoly on the material grade 1 arithmetic operations SD Negeri 1 Kedungsuren? whether learning math games using assisted media monopoly on the material grade 1 arithmetic operations SD Negeri 1 Kedungsuren achieve mastery? and how much influence the outcomes of interest in learning math games using assisted media monopoly on the material grade 1 arithmetic operations SD Negeri 1 Kedungsuren?. Goals to be achieved in this study was to determine the effectiveness of methods of assisted media monopoly game against the interest and learning outcomes of students in grade I arithmetic operations SD Negeri 1 Kedungsuren Kendal. Method in this study is experimental. Design research is the design of a pretest-posttest control group. Results of analysis using t-test values ?óÔé¼ÔÇ??óÔé¼ÔÇ?obtained t >?é?á t table or 2.35 > 2.04 so there is a difference in student learning outcomes using the game through the media monopoly with students with learning learning outcomes lecture method. Results of data analysis indicated the research by obtaining t > t table or 3.44 > 2.13 indicates that the learning using the game of aided the media monopoly has been able to achieve mastery learning. Students' interest in learning using the game of monopoly media aided affect student learning outcomes. This is indicated by a simple regression analysis to = -60.37 +1.638 X and the coefficient of determination R2 of 0.612 or 61.2%. This means that students' interest in learning the game using assisted media monopoly influence on learning outcomes was 61.2%. It can be concluded that the method assisted media monopoly game effectively against the material interests and learning outcomes grade 1 arithmetic operations SD Negeri Kedungsuren Kendal. The suggestion that teachers should be submitted using the methods of the game assisted learning media monopoly.